FUNGSI KELUARGA DAN KUALITAS HIDUP LANSIA - Anita, Ria; Induniasih (Jurnal Media Ilmu Kesehatan, 2013)
Background: In the year 2010 resident lansia in Indonesia reach 23,9 million or 9,77% and spark age of life become 67,4 year. Year 2020 estimate of resident lansia in Indonesia reach 28,8 million or 11,34% with the spark age of life about 71,1 year (Departmental of Health RI, 2005). Daerah Istimewa Yogyakarta (DIY) in this time there are 43.800 people lansia or almost 9% from amount of resident (Statistical Center Body of Indonesia, 2009). According to Whinney (1989) form of cycle and family function as a whole have the big influence to health of every family member especially family by lansia. Antecedent study in Orchard Geblagan show the amount lansia of counted 249 soul, counted 60 soul is men and 189 soul is woman and also most lansia still produktive. Objective: Purpose is to know the relation of between family function by the quality of life at lansia in Orchard of Geblagan Tamantirto Kasihan Bantul Yogyakarta Methods: Method in this research is analytic descriptive by using approach of cross sectional. Sample taken with the technique of cluster random sampling that is 89 lansia which have age to 60 year in Orchard Geblagan. Research instrument is kuesioner and result of research analysed with the formula of correlation of Kendall Tau. Result: Family function at lansia in Orchard of Geblagan Tamantirto Kasihan Bantul most is goodness of counted 54 people (60,7%). Quality of life lansia in Orchard of Geblagan Tamantirto Kasihan Bantul most is] counted 42 people (47,2%). Result test the correlation of Kendal Tau obtained p-value of equal to 0,000 < (0,05). Conclusion: There is relation between family function with the quality of life lansia in Orchard of Geblagan Tamantirto Kasihan Bantul Yogyakarta. Keywords: Function Family, Quality of Life Lansia